KESIAPAN CALON GURU OTOMOTIF DALAM MENGIMPLEMENTASIKAN MATERI KENDARAAN LISTRIK - Hasna Nailah Luthfiyah; Reni Anggraeni; Wahid Munawar (LPPM Universitas Cipta Mandiri, 2026)
The development of electric vehicle technology encourages the readiness of Automotive Engineering Education students as future educators in implementing materials relevant to industrial needs. This study aims to analyze student readiness in implementing electric vehicle materials based on aspects of conceptual knowledge, technical skills, and pedagogical readiness. This study used a quantitative descriptive approach with 56 students selected using a purposive sampling technique. Data collection was conducted using a Likert scale questionnaire that had been tested for validity and reliability. The results showed that the majority of students were in the ready and very ready categories at 77 percent. The highest readiness was found in the aspect of conceptual knowledge, followed by pedagogical readiness and technical skills. Although all respondents had practical experience through the Professional Strengthening Program for Education and Industrial Practice, student readiness was not fully evenly distributed. These findings indicate that practical experience needs to be supported by the quality and relevance of learning so that student readiness in implementing electric vehicle materials can be optimal.